Two at once: simultaneous increased production of astaxanthin and mycosporines in a single Batch culture using a Phaffia rhodozyma mutant strain - Moliné, Martín (2024)
Phaffia rhodozyma is a basidiomycetous yeast characterized by its production of the carotenoid pigment astaxanthin, which holds high commercial value for its significance in aquaculture, cosmetics and as nutraceutics, and the UV-B-absorbing compound mycosporine-glutaminol-glucoside (MGG), which is of great biotechnological relevance for its incorporation into natural sunscreens. However, the industrial exploitation has been limited to the production of astaxanthin in small quantities. On the other hand, the accumulation of MGG in P. rhodozyma was recently reported and could add value to the simultaneous production of both metabolites. In this work, we obtain a mutant strain that overproduces both compounds, furthermore we determined how the accumulation of each is affected by the carbon-to-nitrogen ratio and six biotic and abiotic factors. The mutant obtained produces 159% more astaxanthin and 220% more MGG than the parental strain. Furthermore, we establish that the carotenoids accumulate during the exponential growth phase while MGG accumulates during the stationary phase. The carbon-to-nitrogen ratio affects each metabolite differently, high ratios favoring carotenoid accumulation while low ratios favoring MGG accumulation. Finally, the accumulation of both metabolites is stimulated only by photosynthetically active radiation and low concentrations of hydrogen peroxide. The mutant strain obtained is the first hyper-productive mutant capable of accumulating high concentrations of MGG and astaxanthin described to date. The characterization of how both compounds accumulate during growth and the factors that stimulate their accumulation, are the first steps toward the future commercial exploitation of strains for the simultaneous production of two biotechnologically important metabolites.